EFIKASI DIRI DAN GENDER PADA PRESTASI BELAJAR - Anderson, Elisa (Klabat Journal of Nursing, 2022)
ABSTRACT The individual's belief in himself that he can complete something he is living is self-efficacy and gender is one of the discriminations in nursing services. In nursing student learning achievement, self-efficacy and gender play a role in their achievement. The purpose of this study was to analyze the effect of self-efficacy and gender on learning achievement. This research method is cross-sectional involving 301 respondents through consecutive sampling technique. The results of this study were that the students' self-efficacy was good 153 (50.8%), most respondents were 255 women (84.7%), and the highest learning achievement was very good 147 (48.9). Self-efficacy has a significant relationship (p=0.010; p<0.05) and gender has no significant relationship (p=0.326; p>0.05) on learning achievement. Further research by adding other independent variables needs to be done to find out other factors related to learning achievement, and multivariate analysis needs to be done to find out how much influence these factors have on learning achievement. KEYWORDS: gender, learning achievement, self-efficacy ABSTRAK Kepercayaan individu terhadap dirinya bahwa dapat menyelesaikan sesuatu yang sedang dijalaninya adalah efikasi diri dan gender merupakan salah satu diskriminasi dalam pelayanan keperawatan. Pada prestasi belajar mahasiswa keperawatan, efikasi diri dan gender berperan dalam pencapaiannya. Tujuan penelitian ini adalah menganalisis pengaruh efikasi diri dan gender terhadap prestasi belajar. Metode penelitian ini adalah cross-sectional yang melibatkan 301 responden melalui teknik consecutive sampling. Hasil penelitian ini adalah efikasi diri mahasiswa adalah baik 153 (50,8%), responden terbanyak adalah perempuan 255 (84,7%), serta prestasi belajar terbanyak adalah sangat baik 147 (48,9). Efikasi diri mempunyai hubungan yang bermakna (p=0,010; p<0,05) dan gender tidak mempunyai hubungan yang bermakna (p=0,326; p>0,05) terhadap prestasi belajar. Penelitian lanjutan dengan menambahkan variabel independen lainnya perlu dilakukan untuk mengetahui faktor-faktor lain yang berhubungan dengan prestasi belajar, serta perlu dilakukan analisis multivariat untuk dapat mengetahui seberapa besar pengaruh faktor-faktor tersebut terhadap prestasi belajar. KATA KUNCI: efikasi diri, gender, prestasi belajar